Enhanced propagation of intracellular and extracellular antibiotic resistance genes in municipal wastewater by microplastics. (1st January 2022) - Cheng, Yuan; Lu, Jiarui; Fu, Shusen; Wang, Shangjie; Senehi, Naomi; Yuan, Qingbin
Abstract: Microplastics (MPs) are an emerging global concern as they are abundant in the environment and can act as vectors of various contaminants. However, whether and how MPs can be vectors of antibiotic resistance genes (ARGs), especially extracellular ARGs (eARGs), remains far from explicit. This study addresses the adsorption of both intracellular ARGs (iARGs) and eARGs by four types of MPs in municipal wastewater, and then explores the potential horizontal gene transfer of iARGs and eARGs exposed to MPs. Results indicate that though MPs significantly adsorbed both iARGs and eARGs, eARGs were adsorbed with a significantly higher fold enrichment (2.0–5.0 log versus 2.0–3.3 log) and rate (0.0056 min −1 versus 0.0037 min −1 ) than iARGs. While all four types of MPs adsorbed ARGs, polypropylene MPs showed the highest adsorption capacity for ARGs. Background constituents such as humic acid and antibiotics significantly inhibited adsorption of iARGs, but not eARGs on MPs. The presence of sodium chloride didn't significantly affect adsorption of iARGs or eARGs. The adsorption of ARGs was well explained by the extended Derjaguin–Landau–Verwey–Overbeek (XDLVO) interaction energy profile. Higher eARG adsorption was attributed to a lower energy barrier between MPs and eARGs than that between MPs and iARGs. Exposure to MPs enhanced horizontal gene transfer of both iARGs and eARGs by 1.5 and 2.0 times, respectively. The improved contact potential between donors and recipients, as well as the increased cell permeability of recipients induced the improved horizontal gene transfer by MPs. This study underscores the need to address ARG propagation through adsorption to MPs. Graphical abstract: Image 1 Highlights: Extracellular ARGs are adsorbed at higher fold and rate than intracellular ARGs. Polypropylene have the highest adsorption capacity of ARGs among all microplastics. Pollutants alleviate adsorption of intracellular but not extracellular ARGs. The interaction energy well explains the adsorption of ARGs by microplastics. Exposure to microplastics enhances horizontal gene transfer of ARGs.